Learning Difficulties Among Slow Learners in Primary School: A Case Study at SD Negeri Giling 03 - Ulya Gufroni; Reno Widayati; Nur Zuafah; Rohana Quddus; Indah Lestari (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The implementation of inclusive education requires schools to provide equitable learning opportunities for all students, including those identified as slow learners. Although these students generally do not exhibit significant physical differences from their peers, they often experience cognitive, academic, social, and communication challenges that affect their learning outcomes. This study aims to analyze the learning difficulties experienced by slow learners in an inclusive primary school and to identify the factors contributing to these challenges. A qualitative case study approach was employed involving three slow learner students enrolled in Grade III of an inclusive primary school. Data were collected through classroom observations, in-depth interviews with classroom teachers, special education teachers, and parents, as well as document analysis. The data were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings reveal that slow learners encounter difficulties in understanding instructional content, maintaining working memory, developing literacy and numeracy skills, sustaining attention, and engaging in effective communication and social interaction. Furthermore, limited individualized instructional support, insufficient implementation of inclusive teaching strategies, and inconsistent collaboration between schools and families contribute to the persistence of these learning difficulties. The study highlights the importance of implementing differentiated instruction, the Universal Design for Learning (UDL) framework, strengthening the role of special education teachers, and fostering effective school–family partnerships to improve learning outcomes for slow learners. These findings provide practical implications for enhancing inclusive education policies and instructional practices in primary schools.